Gold colitis induced by auranofin treatment of rheumatoid arthritis: case report and review of the literature. Issue 10 (October 1987) - Langer, H E; Hartmann, G; Heinemann, G; Richter, K
Abstract : A case of ulcerative colitis occurred during treatment of rheumatoid arthritis with the new oral gold preparation auranofin after a cumulative dose of 2160 mg. A barium enema showed loss of mucosal pattern and a rectal biopsy disclosed deep erosions, mucosal inflammation, and crypt abscesses. Precipitates of gold were seen in the periglandular stroma. On electron microscopy the gold deposits seemed to be identical to granules described in gold nephropathy. As the extrapolated serum gold level was within the normal range at the onset of the complication, the morphological findings suggested a local toxicity of the drug. The patient recovered within 14 days of withdrawal of auranofin and the start of therapy with sulphasalazine and steroids. A review of the published work shows that the previously reported mortality in gold colitis of 40% has decreased in recent years. The causes of this decrease may be both the earlier diagnosis of gold colitis and the improved intensive care of its severe complications.